A smuggling bishop - Ayala Olazával, José Luis (2020)
The present article explains the historical events and characters that Ricardo Palma recorded in his tradition “Un obispo de contrabando”, whose anecdote took place in Cusco in 1620. It also offers an approach to some of the historical sources from which our author learned to build the tradition of the fake bishop, who endowed with great sacred oratory claimed to have been presented by the king of Spain to be the bishop of Caracas.